The Mass Hierarchy in the Relativistic Uniform System (Bulletin of Pure and Applied Sciences – Physics, 2019)
The analysis of the relativistic uniform system in the framework of the covariant  theory of gravitation leads to five different masses of the physical system, in  which the particles are bound together by means of the electromagnetic and  gravitational fields, the acceleration field and the pressure field. In this case it  turns out that the system’s gravitational mass is equal to the sum of the invariant  masses of all the system’s particles, and the system’s inertial mass is less than the  gravitational mass by the value of the system’s binding mass-energy.